Engaging common property theory: implications for benefit sharing research in developing countries. Issue 1 (February 2012) - Nkhata, Bimo Abraham; Breen, Charles; Mosimane, Alfons
This article discusses the research relevance of benefit sharing and its implications for natural resource policy research in developing countries. It argues that the research challenge is how to improve understanding of benefit sharing policies by way of identifying the basic principles which underlie these policies. While benefit sharing is to a large extent context dependent, the central question we raise is whether we can identify a set of principles to enable one to describe, explain, understand and predict outcomes in relevant policy settings.